Infectious complications and ventilation tubes in pediatric cochlear implant recipients. (7th September 2015) - Javia, Luv; Brant, Jason; Guidi, Jessica; Rameau, Anaïs; Pross, Seth; Cohn, Samuel; Kazahaya, Ken; Dunham, Brian; Germiller, John
Abstract : Objectives/Hypothesis: At many centers, ventilating tubes (VTs) are placed routinely in otitis‐prone pediatric cochlear implant recipients. However, this practice is controversial, as many otologists believe VTs represent a possible route for contamination of the device. Toward better understanding of the safety of VTs, we reviewed our center's infectious complications and their relationship to the presence of tubes. Study Design: Retrospective cohort study. Methods: All patients undergoing cochlear implantation at our institution between 1990 and 2012 were reviewed for complications and their association with the presence of VTs. Results: A total of 478 patients (557 ears) were reviewed, representing over 2, 978 patient‐years of follow‐up. In 135 ears (24.2%), a VT was present at time of, or placed at some point after, implantation. The remainder either never had a VT or it had extruded prior to implantation. Overall, 63 complications occurred, of which 17 were infectious. The most common were cellulitis (four), device infection (five), and meningitis (four). Only one occurred while a tube was present, and was a device infection in an ear having a retained VT in place for almost 4 years. No difference was observed in overall rates of infectious complications between the group with VTs and those who never had VTs. Conclusions: This series, the largest to date, indicates that infectious complications after cochlear implantation are rarely associated with the presence of VTs, supporting the concept that, overall, VTs are safe in cochlear implant recipients. Close monitoring is essential, including prompt removal of tubes when they are no longer needed. Level of Evidence: 4. Laryngoscope, 126:1671–1676, 2016